IMPLEMENTASI OTONOMI DAERAH TERHADAP POTENSI DESA CARAWALI KECAMATAN WATANG PULU KABUPATEN SIDENRENG RAPPANG - Muh Muttakin (PRAJA: Jurnal Ilmiah Pemerintahan, 2018)
The purpose of the study is to find out how the implementation of autonomy on the potential of Carawali village, Watang Pulu district, Sidenreng Rappang district and to find out the factors that influence the implementation of autonomy on the potential of Carawali village, Watang Pulu district, Sidenreng Rappang district.The population of this study was 649 heads of families, while the research sample was taken from 10% of 649 heads of families, which amounted to 65 heads of families. The data collection technique used in this research is to use the techniques (1) Observation, (2) Interview, (3) Research Library. and (4) Questionnaire. The collected data is then analyzed using frequency and percentage tables. The results of this study indicate that the implementation of Autonomy on the Potential of Carawali Village, Watang Pulu District, Sidenreng Rappang Regency with a value of 68.67% went well. The factors that influence the implementation of autonomy on the potential of Carawali Village, Watang Pulu District, Sidenreng Rappang Regency, namely the policy standard factor 72%, the policy target factor 70%, the resource factor 69%, the implementing organization characteristic factor 68%, the attitude factor of the implementers 71%, Communication factors between organizations related to implementation activities are 70%, social environmental factors are 72%, economic factors are 65%, political factors are 68% with 69.44% achievements categorized as good.